2002
DOI: 10.1002/erv.501
|View full text |Cite
|
Sign up to set email alerts
|

Night time eating: a review of the literature

Abstract: This study reviews the published research on night time eating, including the night eating syndrome (NES) and the nocturnal eating/drinking syndrome (NEDS). Studies were identified by a computerized literature search (PubMed, PsycInfo) and by references from the papers obtained. In addition, published abstracts from recent conferences in the areas of eating disorders and obesity were included. Individual studies were reviewed and their results summarized. Wakeful night time eating appears to be a frequent symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
3
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 37 publications
1
74
3
4
Order By: Relevance
“…This idea is indirectly supported by the long history of unsuccessful weight loss attempts usually reported by night eaters. 32 The few available data indicate a potential beneficial effect of sertraline, 33 cognitive behavior therapy 34 and relaxation training, 35 but we still lack large randomized trials to evaluate the role of these procedures in the management of NES associated with morbid obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is indirectly supported by the long history of unsuccessful weight loss attempts usually reported by night eaters. 32 The few available data indicate a potential beneficial effect of sertraline, 33 cognitive behavior therapy 34 and relaxation training, 35 but we still lack large randomized trials to evaluate the role of these procedures in the management of NES associated with morbid obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of NES have employed variations of these criteria (see de Zwaan, Burgard, Schenck, & Mitchell, 2003 for review), including the use of different cut-times for evening hyperphagia: 7 pm (Cerú-Björk, Andersson, & Rössner, 2001;Striegel-Moore, Franko, Thompson, Affenito, & Kraemer, 2006;Stunkard et al, 1996), after the evening meal (Birketvedt et al, 1999, Marshall, Allison, O'Reardon, Birketvedt, & Stunkard, 2004O'Reardon et al, 2004), after 11pm (Striegel-Moore et al, 2006), and simply, evening eating (Kuldau & Rand, 1986;Rand et al, 1997). The proportion of calories used to define evening hyperphagia has also varied by study, from 25% (Stunkard et al, 1955, Allison, Grilo, Masheb, & Stunkard, 2005 to 50% (Birketvedt et al, 1999;Stunkard et al, 1996), to simply overeating or excessive eating during the evening (Kuldau & Rand, 1986;Rand, MacGreggor, & Stunkard, 1997).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…NES prevalence estimates are low in community samples (range: 0.4-1.6%), 5,17,18 but markedly higher among groups of obese persons seeking medical or surgical weight loss (range: 6-64%). 19 Despite this, only one cross-sectional study has shown a positive relationship between NES and body mass index (BMI). 20 Symptoms of depression are more consistently associated with NES, 1,4,7 but may be influenced by the concurrence of binge eating disorder (BED).…”
Section: Introductionmentioning
confidence: 99%